IDENTIFIKASI WAJAH BERBASIS SEGMENTASI WARNA KULIT WAJAH MENGGUNAKAN NAIVE BAYES CLASSIFIER - Putra, Dimas Rossiawan Hendra; Marisa, Fitri; Wijaya, Indra Dharma (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Face Identification is an important part in digital image processing techniques to determine the size, location and image value. Face detection is a step in the facial recognition system used for personal identification, monitoring system, criminal law, human and computer interaction and so on. This study featuring face detection using Naïve Bayes Classifier with red, green and blue (RGB) model features. This study uses images with variation of facial expression from training data and testing data. The first step is to create a model of facial skin color with RGB model feature which has done normalization process bygrayscaling image, binarying image and filtering image using max filter, then looking for average RGB color of facial skin, followed by building Gaussian distribution showing skin color classification and processed by Naïve method Bayes Classifier (NBC) in determining the classification result.From the test results with a total of 70 test data and a threshold of 0.1, the results of system accuracy reaches 90.25%.